ANALISIS PEMBENTUKAN CADANGAN SEBELUM DAN SESUDAH PENERAPAN METODE IMPAIRMENT TERHADAP KINERJA KEUANGAN PT. BANK NEGARA INDONESIA (PERSERO) - Imelda, Tjut Meutia (Fakultas Ekonomi Universitas Djuanda, 2016)
Changes in Accounting Guidelines for Indonesian Banking (Pedoman Akuntansi Perbankan Indonesia / PAPI) after a revision of PSAK No. 55 of 2008 on the establishment of allowance for losses using impairment methods, give the phenomenon that the backup can be processed to enhance and improve financial performance. Based on the research results, revealed that in 2007, prior to the declaration of regulatory changes regarding loss reserves, BNI financial performance conditions seem low, the low Return on Assets, Return on Equity and the Minimum Capital Requirement and the high of the ratio of Operating Expenses to Operating Income and Non Performing Loan.Growth of allowance forlosses established by BNI seen to decline during the transition period ofimpairment method application. During the transitional period of implementation (2009-2011) shows that the method of impairment impact on the financial performance of growth is so high and good, especially the customer deposits, income for the year, earnings per share, Return on Asstes, Return on Equity, and the Minimum Capital Requirement and low of Operating Exepenses compared to Operating Income and Non Performing Loans. After the transitional period of impairment method aplication (2011), the ratio of loan loss reserves established against the loan is below average. With the implementation of the policy by using impairment methods of allowance for losses can help BNI to fix and improve their financial performance.Keywords: PPAP, CKPN, Allowance for Losses, Impairment Method, Bank Financial Performance.